The Tyranny of Utility : Behavioral Social Science and the Rise of Paternalism - Saint-Paul, Gilles (Book collections on Project MUSE., 2011)
The general assumption that social policy should be utilitarian--that society should be organized to yield the greatest level of welfare--leads inexorably to increased government interventions. Historically, however, the science of economics has advocated limits to these interventions for utilitarian reasons and because of the assumption that people know what is best for themselves. But more recently, behavioral economics has focused on biases and inconsistencies in individual behavior. Based on these developments, governments now prescribe the foods we eat, the apartments we rent, and the com.